Charge separation and molecule activation promoted by Pd/MIL-125-NH2 hybrid structures for selective oxidation reactions. Issue 1 (3rd December 2019) - Wang, Ting; Tao, Xueqin; Xiao, Yi; Qiu, Ganhua; Yang, Yun; Li, Benxia
Abstract : The Pd/MIL-125-NH2 hybrid photocatalyst exhibits great advantages in charge separation and molecule activation, with sufficient generation of both superoxide radical and singlet oxygen toward selective oxidation of organic molecules. Abstract : While heterogeneous photocatalysis is regarded as a sustainable strategy to achieve organic reactions for the production of high-value-added organics, photocatalytic efficiency is generally limited by poor charge separation, dull surface catalytic activity and the consequently caused insufficient generation of active species. Herein, the hybrid structures of metal–organic frameworks (MOFs) incorporated with Pd ultrasmall nanocrystals are synthesized, and their photocatalytic performance is evaluated by the oxidative coupling of benzylamine as a model reaction. The photocatalytic activity of the Pd/MIL-125-NH2 hybrid material with an optimal Pd loading is greatly superior to that of the pristine MIL-125-NH2, achieving a high benzylamine conversion rate of 3136 μmol h −1 gcat −1 at 94.08% conversion. The enhanced charge transfer and separation in Pd/MIL-125-NH2 are verified by photoluminescence spectroscopy and photoelectrochemical experiments. Photogenerated reactive oxygen species are probed by 3, 3′, 5, 5′-tetramethylbenzidine (TMB) as an indicator and the reactive intermediates in the photocatalytic systems are identified by in situ ESR detection. The results confirm that the optimized Pd/MIL-125-NH2 hybrid catalyst possesses higher ability for molecule activation and that both superoxide radical (˙O2 − ) and singlet oxygen ( 1 O2 ) are the dominant oxidative species in the present photocatalytic system. Therefore, the dual advantages of Pd/MIL-125-NH2 hybrid structures for promoting the photogenerated charge transfer/separation and providing highly catalytic sites for molecule activation contribute to higher photocatalytic activity.